2005
DOI: 10.1111/j.1464-5491.2005.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and reliability of hypoglycaemic episodes recorded with Continuous Glucose Monitoring System (CGMS) in daily life

Abstract: Hypoglycaemic episodes recorded by CGMS are reproducible and agreement with independent SMBG values is acceptable for retrospective recording of hypoglycaemic events with CGMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
1
29
0
3
Order By: Relevance
“…Though we tried to select a group of type 1 diabetic patients who were relatively free of complications, it is possible that some of the older participants and those with a longer disease duration could have had occult or undiagnosed coronary artery disease. CGM systems may be less accurate than direct measurement of glucose, though the CGMS we used has been validated at low glucose levels [7]. Nevertheless, our research has confirmed that QTc lengthening and ECG abnormalities occur during naturally occurring nocturnal hypoglycaemia in patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Though we tried to select a group of type 1 diabetic patients who were relatively free of complications, it is possible that some of the older participants and those with a longer disease duration could have had occult or undiagnosed coronary artery disease. CGM systems may be less accurate than direct measurement of glucose, though the CGMS we used has been validated at low glucose levels [7]. Nevertheless, our research has confirmed that QTc lengthening and ECG abnormalities occur during naturally occurring nocturnal hypoglycaemia in patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 66%
“…The mean absolute difference between sensor and meter glucose values was 18.4% vs 16.1%, and the Bland-Altman analysis showed a median bias of −0.1 (range −1.4 to 1.1) [6]. The system has also been shown to be accurate at hypoglycaemic levels [7]. The CGMS was calibrated in a standard way as recommended by the manufacturer, using four validated self-monitored blood glucose levels during the 24 h monitoring periods.…”
Section: Methodsmentioning
confidence: 91%
“…Data files were generated by means of the most recent Medtronic MiniMed CGMS software, version 1.7A. Graphs were initially evaluated to identify periods with valid data, which were defined as the interval between first entered calibration value and last accepted calibration value [7]. We discarded periods containing less than four calibrations in 24 h and periods with no electrical signal.…”
Section: To the Editormentioning
confidence: 99%
“…Hypoglycaemic nights were defined by CGMS glucose readings of 2.2 mmol/l (lower detection limit of the CGMS) lasting for at least 10 min. Such episodes represent true hypoglycaemia with an 84% probability, when compared with conventional blood glucose measurements [7]. Possibly hypoglycaemic nights were defined by nadir CGMS glucose readings of 2.3-3.5 mmol/ l, and non-hypoglycaemic nights by nadir glucose readings T. Høi-Hansen (*) .…”
mentioning
confidence: 99%
“…Исследования нарушений уровня гликемии в ночной период у детей для выявления риска внезапной смерти проводятся в настоящее время преимущественно при диабете 1-го и 2-го типа [11][12][13]. В качестве предиктора ночных гипогликемий и риска вне-запной смерти у молодых взрослых при диабете и СОАС была предложена дневная сонливость [14].…”
Section: актуальные вопросы педиатрии обоснованиеunclassified